Abscisic acid mediates hydrogen peroxide production in peanut induced by water stress - Furlan, Ana Laura (2012)
Peanut plants exposed to water stress induced by polyethylene glycol (PEG) accumulated abscisic acid (ABA) and hydrogen peroxide (H2O2), the increase being significant at 12 and 24 h after addition, respectively. To address the question whether the increase in H2O2 production was related to ABA accumulation, the peanut leaves were pretreated with ABA biosynthesis inhibitor (sodium tungstate) and then exposed to water stress. Under these conditions, a decrease of ABA and H2O2 content were found after 12 h. The addition of 100 µM ABA restored H2O2 content reaching values similar to those under water stress at 12 h. We concluded that ABA accumulation is the first signal that triggers the H2O2 generation in peanut during first 12 h but its subsequent production is partially ABA-independent.